Myeloid cell-specific sirtuin 6 deficiency delays wound healing in mice by modulating inflammation and macrophage phenotypes - Koo, Jeung-Hyun (Exp Mol Med, 2019)
We recently reported that myeloid cell-expressed sirtuin 6 (Sirt6) plays a crucial role in M1 macrophage polarization and chemotaxis. Given the prominent role of macrophages during wound repair and macrophage heterogeneity, we hypothesized that a Sirt6 deficiency in myeloid cells would delay skin wound closure by affecting the phenotypes of macrophages in wounds. To address this question, a full-thickness excisional lesion was made in the dorsal skin of myeloid cell-specific Sirt6 knockout (KO) and wild-type mice. Wound closure was delayed in the KO mice, which exhibited less collagen deposition, suppressed angiogenesis, and reduced expression of wound healing-related genes compared to the wild-type mice. Using immunohistochemical, flow cytometric, and gene-expression analyses of macrophage subpopulations from wound tissue, we identified increased infiltration of M1 macrophages with a concomitant decrease in M2 macrophage numbers in the KO mice compared to the wild-type mice. Consistent with the in vivo wound closure defects observed in the KO mice, keratinocytes and fibroblasts treated with KO macrophage-derived conditioned medium migrated slower than those treated with wild-type macrophage-derived conditioned medium. An analysis of downstream signaling pathways indicated that impaired Akt signaling underlies the decreased M2 phenotypic switching in KO mice. These results suggest that a macrophage phenotypic switch induced by Sirt6 deficiency contributes to impaired wound healing in mice.